Nutrient dynamics and buffering capacity of coastal groundwater-dependent microbialite ecosystems - Carla Dodd; Hayley C. Cawthra; Gudrun Massmann; Janine B. Adams; Callum R. Anderson; Lucienne R.D. Human; Daniel A. Lemley; Tristin W. O'Connell; Gavin M. Rishworth (Estuarine, Coastal and Shelf Science, 2026)

Per- and polyfluoroalkyl substances, vitamin D, and risk of preterm birth in a Canadian cohort - Mandy Fisher; James Owen; Leonora Marro; Beth Potter; Hope A. Weiler; Gillian England-Mason; Michael M. Borghese; Mark Walker; Linda Dodds; Michael Helewa; Tye E. Arbuckle; Bruce Lanphear; et al. (Environmental Research, 2026)

Per- and polyfluoroalkyl substances (PFAS) and heavy metals in the egg of peregrine falcon (Falco peregrinus) populations in West England, United Kingdom - Shinji Ozaki; Jacqueline S. Chaplow; Beverley Dodd; Helen Grant; M. Glória Pereira; Elaine Potter; Richard G. Sale; Darren Sleep; Sarah Thacker; Steve J. Watson; Lee A. Walker; Suzane M. Qassim (Ecotoxicology, 2026)

Sector expert and public perceptions of greening of grey infrastructure: a case study in Britain’s Ocean City - Jessica R. Allen; Anaëlle J. Lemasson; Melanie J. Bishop; Katherine A. Dafforn; Kate C. Dodds; Mick E. Hanley; Antony M. Knights; Mariana Mayer-Pinto; Abigail McQuatters-Gollop; Maria L. Vozzo; Louise B. Firth (Urban Ecosystems, 2026)

Genomic, morphological and migratory patterns in recovering Atlantic salmon populations - Paolo M Moccetti; Domino A. Joyce; Jonathan D. Bolland; Jamie R. Dodd; Andy D. Nunn (Aquatic Sciences, 2026)
Population recovery is a key goal for conservation, but our understanding of how genetic and phenotypic variation, including local adaptation, emerges in recently recolonised or recovering systems is limited. This complicates the conservation of fitness-related traits that support resilience and long-term population viability. We employed single nucleotide polymorphism markers, geometric morphometrics and acoustic telemetry to investigate the recovery of Atlantic salmon ( Salmo salar ) in a large river system, which began more than 40 years ago following presumed extirpation in the mid-1900s. We observed genetic differentiation between Atlantic salmon in different tributaries that may reflect natural recolonisation through straying and/or the recovery of remnant populations previously believed to be extinct. Fine-scale philopatry was found to maintain the genetic divergence between tributaries, as confirmed by genetic assignment and telemetry tracking of returning adults, with some individuals displaying ‘search’ behaviour across tributaries. Despite this population structuring, neither consistent genomic signatures of selection nor morphological divergence were detected, indicating no evidence for early stage local adaptation or for differing selective pressures between tributaries. The patterns instead align with stochastic demographic processes (i.e. founder effects and genetic drift), which was further supported by the low contemporary effective population sizes detected across tributaries. These findings highlight the importance of continued genomic and ecological monitoring during population recovery, as improving environmental conditions may promote the re-establishment of remnant populations and/or facilitate recolonisation. This may, in turn, lead to the formation of reproductively isolated units and, over time, the emergence of locally adapted traits of conservation value for Atlantic salmon and other threatened migratory species.

Do artificial roost design and placement alter the torpor expression of Indiana bats? - Reed D. Crawford; Luke E. Dodd; Joy M. O'Keefe (Journal of Thermal Biology, 2026)

Genomic Architecture of Inbreeding Depression Associated With Hatching Failure in an Endangered Parrot - Yasmin Foster; Stefanie Grosser; Brodie J. Foster; Nicolas Dussex; Aimee Stubbs; Ludovic Dutoit; Theo Atkinson; Fiona Robertson; Ken G. Dodds; Rudiger Brauning; Jeanne M. E. Jacobs; John C. McEwan; et al. (Molecular Ecology, 2026)
Conservation management of endangered species increasingly relies on genomic approaches to understand how long‐term small population sizes affect the fitness of extant individuals. However, despite the growing investment in genomic resources by conservation programmes, the impact that sequencing methods have on the ability to detect inbreeding‐related phenomena has been largely overlooked. Here, we compare the use of whole‐genome and reduced‐representation sequencing approaches in 148 individuals of the critically endangered parrot, the kākāpō ( Strigops habroptilus ), to assess inbreeding and its effects on female reproductive success. We explore how sequencing choice influences the identification of long stretches of homozygosity across the genome (runs of homozygosity, ROH), and compare the conservation implications of the results produced by each method. Both whole‐genome and reduced‐representation sequencing approaches provided comparable estimates of genome‐wide inbreeding ( F ROH ) and revealed consistent effects on egg hatching success, suggesting that reduced‐representation sequencing is capable of detecting inbreeding depression in wild populations under certain conditions. Whole‐genome sequencing enabled chromosome‐level inbreeding analyses, which revealed no strong evidence of chromosome‐specific effects beyond the genome‐wide signal. These results suggest that inbreeding depression in kākāpō reflects small effects across many chromosomes rather than strong effects on only a few, and that the primary benefit of whole‐genome sequencing lies in improving the precision of genome‐wide inbreeding estimates rather than identifying chromosome‐specific effects. Our findings highlight the distinct benefits of each sequencing approach in conservation, particularly within the context of resource limitations.

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Predictions of southern migration timing in coastal sharks under future ocean warming - Maria H. Manz; Oliver N. Shipley; Robert M. Cerrato; Robert E. Hueter; Alisa L. Newton; John P. Tyminski; Bryan R. Franks; Tobey H. Curtis; Christopher Fischer; Joshua P. Zacharias; Christopher Scott; Keith J. Dunton; et al. (Conservation Biology, 2025)
Projected redistribution of marine species due to ocean warming may undermine current conservation efforts. Yet, there have been few studies on how ocean warming may alter migration timing. Across 5 years of acoustic telemetry data (2018–2022), we determined environmental drivers of southward migration timing for 6 migratory shark species from summer habitats in the Northwest Atlantic Ocean. We then forecasted how migratory timing from 3 regions, between the New England shelf and Mid‐Atlantic Bight, would respond under future sea surface temperatures (SSTs). Photoperiod and SST were strong predictors of southern migration in sharks, but the strength of these effects varied latitudinally. Overall, we found delayed departure dates from summer habitats under future elevated SSTs, indicating prolonged residency in northern habitats (median = ∼12 days). Sandbar sharks ( Carcharhinus plumbeus ) exhibited the largest delay in the onset of southern migrations (median = 29 days), whereas sand tiger sharks ( Carcharias taurus ) and white sharks ( Carcharodon carcharias ) exhibited the smallest delay (median = 1 day). Delays in migration timing of coastal shark species may alter local ecosystem dynamics and challenge current management strategies. These findings illustrate the utility of collaborative data‐sharing networks to expand understanding of broadscale animal movements and contribute to effective species management under a changing climate.

Optimising parent selection in plant breeding: comparing metaheuristic algorithms for genotype building - S. Yadav; S. Dillon; M. McNeil; E. Dinglasan; R. Mago; P. Dodds; L. Hickey; B. J. Hayes (Theoretical and Applied Genetics, 2025)
Stacking desirable haplotypes across the genome to develop superior genotypes has been implemented in several crop species. A major challenge in Optimal Haplotype Selection is identifying a set of parents that collectively contain all desirable haplotypes, a complex combinatorial problem with countless possibilities. In this study, we evaluated the performance of metaheuristic search algorithms (MSAs)—genetic algorithm (GA), differential evolution (DE), particle swarm optimisation (PSO), and simulated annealing (SA) for optimising parent selection under two genotype building (GB) objectives: Optimal Haplotype Selection (OHS) and Optimal Population Value (OPV). Using a diverse wheat population of 583 lines genotyped for 29,972 SNPs, forming 7645 haplotype blocks and phenotyped for stripe rust scores, we assessed each algorithm’s performance across fitness optimisation, convergence speed, and computational efficiency. GA consistently achieved high fitness and rapid convergence, while DE showed robustness but required longer runtime and careful tuning. PSO performed well under the OHS criterion but was less effective for OPV. SA, although computationally lighter, was less consistent in finding optimal solutions. Simulation over 100 breeding cycles showed that OHS outperformed both OPV and GEBV-based selection in long-term genetic gain and diversity retention. OHS maintained heterozygosity and additive variance, which are key for sustainable improvement, while GEBV selection led to early allele fixation. Our findings underscore the potential of GB strategies that prioritise the collective performance of parent sets rather than individual ranking to enhance selection outcomes in genomic-assisted breeding programmes.

Using citizen science photographs to identify reproductive events in an oviparous elasmobranch - Rachel Mawer; Jane Dodd; James Thorburn; Neil M. Burns; David M. Bailey (Journal of Fish Biology, 2025)
Identifying critical habitats is important for the effective management of vulnerable species. Critical habitats, such as mating or nursery grounds, support populations during key life stages and help to maximise reproductive output and population growth. In elasmobranchs, mating often happens over a defined season, suggesting sites associated with this process may only require temporal protection. However, knowledge gaps on such sites exist for many elasmobranchs due to the challenges associated with identifying temporal mating periods, which hinders conservation efforts. Here, we investigated the application of photographs to estimate reproductive timing in an oviparous elasmobranch, the flapper skate ( Dipturus intermedius ), as a non‐invasive and low‐cost alternative to other approaches. Using a pre‐existing citizen science photo‐ID database of over 2000 images, we identified signs of reproductive behaviour: the presence or absence of pelvic swelling, bite wounds and scratch wounds. Statistical models were created for each feature to explore seasonal trends and other parameters explaining their presence. Seasonal trends were present for all features and feature occurrence differed with sex. The occurrence of bite wounds and pelvic swelling in flapper skate peaked over winter and spring months, suggesting a winter–spring mating and egg‐laying period. These results are corroborated by previous reproductive research on the flapper skate, suggesting the applied method is a valid tool to estimate reproductive timing in an elusive elasmobranch. The approach could be applied to other flapper skate populations and other elasmobranch species, helping to close existing knowledge gaps on reproductive behaviours.

Relationship Between Rotational Device Kinematics and Head Kinematics in a Large Animal Model of Traumatic Brain Injury - Declan A. Patton; Ciara S. Grunig; Jessica R. McQuaid; Andrew B. Dodd; Mandy K. Pacheco; Josef M. Ling; Tracey V. Wick; Divyasree Sasi Kumar; Vadim Zotev; Rachel E. Kinsler; Kristy B. Arbogast; Andrew R. Mayer (Annals of Biomedical Engineering, 2025)

A juvenile spinner shark in southern New England: A rare visitor or a sign of change? - Joshua K. Moyer; Jon F. Dodd; Stephen M. Kajiura (Journal of Fish Biology, 2025)
A juvenile spinner shark, Carcharhinus brevipinna , was captured and released in the coastal waters of Rhode Island, USA, where range delineations based on historic records of spinner sharks and the species' congener, the blacktip shark, Carcharhinus limbatus , are plagued by misidentification. The shark in question was within the size range of neonates for C. brevipinna and bore a partially healed umbilical wound. This highlights questions concerning the distribution of nursery habitats for the species along the East Coast of North America and how that may be altered by climate change.

Spatial ecology and population dynamics of brown trout Salmo trutta L. in reservoirs and headwater tributaries - Jamie R. Dodd; Richard A. A. Noble; Andy D. Nunn; Holly M. Owen; Paolo Moccetti; Jonathan P. Harvey; Liam Wallace; Ben Gillespie; Domino A. Joyce; Jonathan D. Bolland (Journal of Fish Biology, 2025)
This investigation compared the spatial ecology and population dynamics of brown trout Salmo trutta L. between reservoirs with (impact; Langsett Reservoir) and without (control; Grimwith Reservoir) barriers to fish movements into headwater tributaries, and the effectiveness of a fish pass intended to remediate connectivity. Passive integrated transponder (PIT) telemetry revealed that fish that emigrated from Langsett and Grimwith tributaries were 1–3 and 0–2 years old, respectively, and predominantly did so in spring and autumn‐early winter in both systems. Weirs at Langsett Reservoir appeared to thwart emigration rate (26%) relative to Grimwith Reservoir (85%). Acoustic telemetry (two‐dimensional positions) in the impacted reservoir revealed that the largest home range was in October–December (95% monthly activity space S.D. up to 26.9 ± 6.69 ha in November), activity was influenced by both month and time of day, and fish occupied shallow water depths (relative to reservoir depth), especially at night. Brown trout tagged in Grimwith and Langsett Reservoirs (42.9% and 64.1%, respectively) and fish tagged in the tributaries that emigrated (37.2% and 27.7%, respectively) were detected immigrating into tributaries throughout the year. At both reservoirs, peak immigration for ≥3‐year‐old trout occurred primarily in autumn‐early winter. Overall passage efficiency went from 3% prior to remediation to 14% after and there was no significant increase in fish densities following the construction of the fish pass. Fish were attracted towards and entered the fish pass under a wide range of river levels, but only succeeded in passing upstream during low levels, which are uncommon druing the main migration period. Overall, this investigation significantly furthers our understanding of brown trout spatial ecology and population dynamics in reservoirs and headwater tributaries.

Fine-scale residency and temperature-driven habitat selection in a migratory shark species - Thorburn J.; Gagnon É.; Martin J.; Henry L.-A.; Wright P.J.; Dodd J.; James M.; Neat F. (Environmental Biology of Fishes, 2025)
Many marine species exhibit complex and diverse movements that vary across spatial and temporal scales. These movements must be accounted for when designing effective management and conservation efforts. While environmental cues such as temperature and salinity have been shown to influence the movements of mobile species, it is increasingly documented that social factors can also influence space use and population behaviour. Understanding how various factors influence movement enhances our ability to predict the space use of highly dynamic ocean species. Spurdog ( Squalus acanthias ), known for their tendency to aggregate and use of both coastal and oceanic environments, are an ideal model species for studying drivers of movement. To investigate movement and habitat selection in spurdog, we conducted an acoustic telemetry study from June 2016 to July 2017, tagging 51 spurdog in a partially enclosed fjordic sea loch on the west coast of Scotland. The thermal profile of Loch Etive was recorded to complement the movement data. Our study revealed temperature as a pivotal driver of movement and habitat selection in spurdog, with the unique thermal environment of the fjord enabling year-round residency at a previously undocumented spatial scale, suggesting that such habitats may be especially important for mobile marine species. This study demonstrates the importance of understanding environmental influences on space use and movement to develop effective, climate-resilient management strategies for spurdog and other mobile marine species.

Factors influencing European river lamprey passage at a tidal river barrier - Angus J. Lothian; Jonathan D. Bolland; Atticus J. Albright; William M. Jubb; Damian H. Bubb; Richard A. A. Noble; Andrew D. Nunn; Jamie R. Dodd; Jeroen S. Tummers; Martyn C. Lucas (Hydrobiologia, 2024)

Clopidogrel Is Associated with Reduced Likelihood of Aneurysmal Subarachnoid Hemorrhage: a Multi-Center Matched Retrospective Analysis - Joseph S. Hudson; Kamil W. Nowicki; Brandon Lucke-Wold; Zachary C. Gersey; William S. Dodd; Ali Alattar; David J. McCarthy; Prateek Agarwal; Zain Mehdi; Michael J. Lang; David M. Hasan; Brian L. Hoh; et al. (Translational Stroke Research, 2024)

Investigating mouse hepatic lipidome dysregulation following exposure to emerging per- and polyfluoroalkyl substances (PFAS) - Kaylie I. Kirkwood-Donelson; Jessie Chappel; Emma Tobin; James N. Dodds; David M. Reif; Jamie C. DeWitt; Erin S. Baker (Chemosphere, 2024)

Construction of relatedness matrices in autopolyploid populations using low-depth high-throughput sequencing data - Timothy P. Bilton; Sanjeev Kumar Sharma; Matthew R. Schofield; Michael A. Black; Jeanne M. E. Jacobs; Glenn J. Bryan; Ken G. Dodds (Theoretical and Applied Genetics, 2024)
Key message An improved estimator of genomic relatedness using low-depth high-throughput sequencing data for autopolyploids is developed. Its outputs strongly correlate with SNP array-based estimates and are available in the package GUSrelate. Abstract High-throughput sequencing (HTS) methods have reduced sequencing costs and resources compared to array-based tools, facilitating the investigation of many non-model polyploid species. One important quantity that can be computed from HTS data is the genetic relatedness between all individuals in a population. However, HTS data are often messy, with multiple sources of errors (i.e. sequencing errors or missing parental alleles) which, if not accounted for, can lead to bias in genomic relatedness estimates. We derive a new estimator for constructing a genomic relationship matrix (GRM) from HTS data for autopolyploid species that accounts for errors associated with low sequencing depths, implemented in the R package GUSrelate. Simulations revealed that GUSrelate performed similarly to existing GRM methods at high depth but reduced bias in self-relatedness estimates when the sequencing depth was low. Using a panel consisting of 351 tetraploid potato genotypes, we found that GUSrelate produced GRMs from genotyping-by-sequencing (GBS) data that were highly correlated with a GRM computed from SNP array data, and less biased than existing methods when benchmarking against the array-based GRM estimates. GUSrelate provides researchers with a tool to reliably construct GRMs from low-depth HTS data.

The special sauce of the Cancer Prevention and Control Research Network: 20 years of lessons learned in developing the evidence base, building community capacity, and translating research into practice - Stephanie B. Wheeler; Rebecca J. Lee; Alexa L. Young; Adam Dodd; Charlotte Ellis; Bryan J. Weiner; Kurt M. Ribisl; Prajakta Adsul; Sarah A. Birken; María E. Fernández; Peggy A. Hannon; James R. Hébert; et al. (Cancer Causes & Control, 2023)
Purpose The Cancer Prevention and Control Research Network (CPCRN) is a national network focused on accelerating the translation of cancer prevention and control research evidence into practice through collaborative, multicenter projects in partnership with diverse communities. From 2003 to 2022, the CPCRN included 613 members. Methods We: (1) characterize the extent and nature of collaborations through a bibliometric analysis of 20 years of Network publications; and (2) describe key features and functions of the CPCRN as related to organizational structure, productivity, impact, and focus on health equity, partnership development, and capacity building through analysis of 22 in-depth interviews and review of Network documentation. Results Searching Scopus for multicenter publications among the CPCRN members from their time of Network engagement yielded 1,074 collaborative publications involving two or more members. Both the overall number and content breadth of multicenter publications increased over time as the Network matured. Since 2004, members submitted 123 multicenter grant applications, of which 72 were funded (59%), totaling more than $77 million secured. Thematic analysis of interviews revealed that the CPCRN’s success—in terms of publication and grant productivity, as well as the breadth and depth of partnerships, subject matter expertise, and content area foci—is attributable to: (1) its people–the inclusion of members representing diverse content-area interests, multidisciplinary perspectives, and geographic contexts; (2) dedicated centralized structures and processes to enable and evaluate collaboration; and (3) focused attention to strategically adapting to change. Conclusion CPCRN’s history highlights organizational, strategic, and practical lessons learned over two decades to optimize Network collaboration for enhanced collective impact in cancer prevention and control. These insights may be useful to others seeking to leverage collaborative networks to address public health problems.

Catchment-wide interactive effects of anthropogenic structures and river levels on fish spawning migrations - William M. Jubb; Richard A.A. Noble; Jamie R. Dodd; Andrew D. Nunn; Paula Schirrmacher; Angus J. Lothian; Atticus J. Albright; Damian H. Bubb; Martyn C. Lucas; Jonathan D. Bolland (Anthropocene, 2023)

Nutrient and stoichiometric time series measurements of decomposing coarse detritus in freshwaters - Caleb J. Robbins; Beth C. Norman; Halvor M. Halvorson; David W. P. Manning; Elliot Bastias; Cristiane Biasi; Allyn K. Dodd; Rebecca A. Eckert; Alice Gossiaux; Jérémy Jabiol; Andrew S. Mehring; Ada Pastor (Ecology, 2023)
Decomposition of coarse detritus (e.g., dead organic matter larger than ~1 mm such as leaf litter or animal carcasses) in freshwater ecosystems is well described in terms of mass loss, particularly as rates that compress mass loss into one number (e.g., a first‐order decay coefficient, or breakdown rate, “ k ”); less described are temporal changes in the elemental composition of these materials during decomposition, with important implications for elemental cycling from microbes to ecosystems. This stands in contrast with work in the terrestrial realm, where a focus on detrital elemental cycling has provided a sharper mechanistic understanding of decomposition, especially with specific processes such as immobilization and mineralization. Notably, freshwater ecologists often measure carbon (C), nitrogen (N), and phosphorus (P), and their stoichiometric ratios in decomposing coarse materials, including carcasses, wood, leaf litter, and more, but these measurements remain piecemeal. These detrital nutrients are measurements of the entire detrital–microbial complex and are integrative of numerous processes, especially nutrient immobilization and mineralization, and associated microbial growth and death. Thus, data relevant to an elemental, mechanistically focused decomposition ecology are available in freshwaters, but have not been fully applied to that purpose. We synthesized published detrital nutrient and stoichiometry measurements at a global scale, yielding 4038 observations comprising 810 decomposition time series (i.e., measurements within a defined cohort of decomposing material through time) to build a basis for understanding the temporality of elemental content in freshwater detritus. Specifically, the dataset focuses on temporally and ontogenetically (mass loss) explicit measurements of N, P, and stoichiometry (C:N, C:P, N:P). We also collected ancillary data, including detrital characteristics (e.g., species, lignin content), water physiochemistry, geographic location, incubation system type, and methodological variables (e.g., bag mesh size). These measurements are important to unlocking mechanistic insights into detrital ontogeny (the temporal trajectory of decomposing materials) that can provide a deeper understanding of heterotroph‐driven C and nutrient cycling in freshwaters. Moreover, these data can help to bridge aquatic and terrestrial decomposition ecology, across plant or animal origin. By focusing on temporal trajectories of elements, this dataset facilitates cross‐ecosystem comparisons of fundamental decomposition controls on elemental fluxes. It provides a strong starting point (e.g., via modeling efforts) for comparing processes such as immobilization and mineralization that are understudied in freshwaters. Time series from decomposing leaf litter, particularly in streams, are common in the dataset, but we also synthesized ontogenies of animal‐based detritus, which tend to decompose rapidly compared with plant‐based detritus that contains high concentrations of structural compounds such as lignin and cellulose. Although animal‐based data were rare, comprising only three time series, their inclusion in this dataset underscores the opportunities to develop an understanding of decomposition that encompasses all detrital types, from carrion to leaf litter. There are no copyright or proprietary restrictions on the dataset; please cite this data paper when reusing these materials.

Determining the feasibility of characterising cellular senescence in human skeletal muscle and exploring associations with muscle morphology and physical function at different ages: findings from the MASS_Lifecourse Study - Leena Habiballa; Adam Hruby; Antoneta Granic; Richard M. Dodds; Susan J. Hillman; Diana Jurk; João F. Passos; Avan A. Sayer (GeroScience, 2023)
Cellular senescence may be associated with morphological changes in skeletal muscle and changes in physical function with age although there have been few human studies. We aimed to determine the feasibility of characterising cellular senescence in skeletal muscle and explored sex-specific associations between markers of cellular senescence, muscle morphology, and physical function in participants from the MASS_Lifecourse Study. Senescence markers ( p16 , TAF (Telomere-Associated DNA Damage Foci), HMGB1 (High Mobility Group Box 1), and Lamin B1) and morphological characteristics (fibre size, number, fibrosis, and centrally nucleated fibres) were assessed in muscle biopsies from 40 men and women (age range 47–84) using spatially-resolved methods (immunohistochemistry, immunofluorescence, and RNA and fluorescence in situ hybridisation). The associations between senescence, morphology, and physical function (muscle strength, mass, and physical performance) at different ages were explored. We found that most senescence markers and morphological characteristics were weakly associated with age in men but more strongly, although non-significantly, associated with age in women. Associations between senescence markers, morphology, and physical function were also stronger in women for HMGB1 and grip strength ( r = 0.52); TAF, BMI, and muscle mass ( r > 0.4); Lamin B1 and fibrosis ( r = − 0.5); fibre size and muscle mass ( r ≥ 0.4); and gait speed ( r = − 0.5). However, these associations were non-significant. In conclusion, we have demonstrated that it is feasible to characterise cellular senescence in human skeletal muscle and to explore associations with morphology and physical function in women and men of different ages. The findings require replication in larger studies.

Radiogenic Pb in xenotime trapped in nanoscale inclusions of apatite during fluid alteration - Cilva Joseph; Denis Fougerouse; Steven M. Reddy; Hugo K.H. Olierook; Tommaso Tacchetto; Allen Kennedy; David W. Saxey; William D.A. Rickard; Steven Denyszyn; Aaron Dodd (Chemical Geology, 2023)

Nutrient and stoichiometry dynamics of decomposing litter in stream ecosystems: A global synthesis - Caleb J. Robbins; David W. P. Manning; Halvor M. Halvorson; Beth C. Norman; Rebecca A. Eckert; Ada Pastor; Allyn K. Dodd; Jérémy Jabiol; Elliot Bastias; Alice Gossiaux; Andrew S. Mehring (Ecology, 2023)
Decomposing organic matter forms a substantial resource base, fueling the biogeochemical function and secondary production of most aquatic ecosystems. However, detrital N (nitrogen) and P (phosphorus) dynamics remain relatively unexplored in aquatic ecosystems relative to terrestrial ecosystems, despite fundamentally linking microbial processes to ecosystem function across broad spatial scales. We synthesized 217 published time series of detrital carbon (C), N, P, and their stoichiometric ratios (C:N, C:P, N:P) from stream ecosystems to analyze the temporal nutrient dynamics of decomposing litter using generalized additive models. Model results indicated that detritus was a net source of N (irrespective of inorganic or organic form) to the environment, regardless of initial N content. In contrast, P sink/source dynamics were more strongly influenced by the initial P content, in which P‐poor litters were sinks for nutrients until these shifted to net P mineralization after ~40% mass loss. However, large variations surrounded both the N and P predictions, suggesting the importance of nonmicrobial factors such as fragmentation by invertebrates. Detrital C:N ratios converged and became more similar toward the end of the decomposition, suggesting predictable microbial functional effects throughout detrital ontogeny. C:P and N:P ratios also converged to some degree, but these model predictions were less robust than for C:N, due in part to the lower number of published detrital C:P time series. The explorations of environmental covariate effects were frequently limited by a few coincident covariate measurements across studies, but temperature, N availability, and P tended to accelerate the existing ontogenetic patterns in C:N. Our analysis helps to unite organic matter decomposition across aquatic–terrestrial boundaries by describing the basic patterns of elemental flows catalyzed by decomposition in streams, and points to a research agenda with which to continue addressing gaps in our knowledge of detrital nutrient dynamics across ecosystems.

A narrative review of nutrient based indexes to assess diet quality and the proposed total nutrient index that reflects total dietary exposures - Alexandra E. Cowan; Shinyoung Jun; Janet A. Tooze; Kevin W. Dodd; Jaime J. Gahche; Heather A. Eicher-Miller; Patricia M. Guenther; Johanna T. Dwyer; Nancy Potischman; Anindya Bhadra; Raymond J. Carroll; Regan L. Bailey (Critical Reviews in Food Science and Nutrition, 2023)

The importance of in-year seasonal fluctuations for biomonitoring of apex predators: A case study of 14 essential and non-essential elements in the liver of the common buzzard (Buteo buteo) in the United Kingdom - Shinji Ozaki; Paola Movalli; Alessandra Cincinelli; Nikiforos Alygizakis; Alexander Badry; Jacqueline S. Chaplow; Daniela Claßen; René W.R. J. Dekker; Beverley Dodd; Guy Duke; Jan Koschorreck; M. Glória Pereira; et al. (Environmental Pollution, 2023)

Impacts of Riparian and Non-riparian Woody Encroachment on Tallgrass Prairie Ecohydrology - Rachel M. Keen; Jesse B. Nippert; Pamela L. Sullivan; Zak Ratajczak; Brynn Ritchey; Kimberly O’Keefe; Walter K. Dodds (Ecosystems, 2023)

Resilience of ecosystem service delivery in grasslands in response to single and compound extreme weather events - Rosalind J. Dodd; David R. Chadwick; Paul W. Hill; Felicity Hayes; Antonio R. Sánchez-Rodríguez; Dylan Gwynn-Jones; Simon M. Smart; Davey L. Jones (Science of The Total Environment, 2023)

Approximation of hindered zonal settling rates for flocculated inorganic/organic composite suspensions in inertial flow conditions - Alexander P.G. Lockwood; Jacob R.L. Rumney; Martyn G. Barnes; Jonathan M. Dodds; Jeffrey Peakall; Timothy N. Hunter (Journal of Water Process Engineering, 2023)

Water mass composition in Fram Strait determined from the combination of 129I and 236U: Changes between 2016, 2018, and 2019 - A.-M. Wefing; N. Casacuberta; M. Christl; P. A. Dodd (Frontiers in Marine Science, 2022)
Changes in the provenance and composition of waters exported from the Arctic Ocean have the potential to impact large-scale ocean circulation processes in the sub-polar North Atlantic. The main conveyor of waters from the Arctic Ocean to lower latitudes is the East Greenland Current (EGC), flowing southward through Fram Strait. It is therefore crucial to determine and monitor the composition of the EGC, a mixture of polar waters of different origins. Here we present a pilot study on the potential of the long-lived anthropogenic radionuclides 129 I and 236 U as tracers of the EGC water mass composition, based on a time series of 236 U and 129 I concentrations measured across Fram Strait in the years 2016, 2018, and 2019. The overall spatial distribution of 236 U and 129 I was similar among the three sampling years, but a decrease in concentration was observed in the upper water column of the EGC. The observed changes could only partly be attributed to the transient nature of the radionuclide signals, but instead pointed to changes in the EGC water mass composition. To investigate these changes, 236 U and 129 I were first combined in a mixing model featuring the endmembers expected in the upper EGC. We distinguished between Pacific Water (PAC), Atlantic Water advected from the Arctic Ocean (ATL), and Atlantic Water recirculating in Fram Strait (RAC). In 236 U- 129 I tracer space, PAC and RAC showed similar tracer signatures, but were well distinguished from ATL. From 2016 to 2018/19, a decrease in the ATL fraction was evident for the upper EGC. Secondly, the respective combination of 236 U and 129 I with salinity showed differences in absolute water mass fractions, but similar temporal trends. Both suggested an increase in PAC of about 20% for the uppermost layer of the EGC (samples with potential densities below 26.5) and an increase in RAC of about 10−20 % for denser samples. 129 I and 236 U, in combination with salinity, were shown to be suitable tracers to investigate water mass composition in Fram Strait, with the advantage that they can distinguish Atlantic Water advected from the Arctic Ocean from that recirculating in Fram Strait.

Prairie stream metabolism recovery varies based on antecedent hydrology across a stream network after a bank‐full flood - Claire M. Ruffing; Allison M. Veach; Anne Schechner; Janine Rüegg; Matt T. Trentman; Walter K. Dodds (Limnology and Oceanography, 2022)
Intermittent streams are characterized by significant periods of low to no flow, yet are also frequently subjected to flashy, high floods. Floods alter ecosystem function and result in variable successional patterns across the stream network. Yet, the timing of restored function after floods in intermittent stream networks is relatively unexplored. We measured recovery of stream ecosystem function using rates of gross primary production (GPP), ecosystem respiration (ER), net ecosystem production (NEP), and the primary production to respiration ratio (P/R) across eight locations in the Kings Creek drainage basin with differing preflood conditions (previously dry [intermittent] or flowing [perennial]) over a 30‐d period following a 2‐yr return interval flood. We found that all metabolic rates (GPP, ER, NEP, P/R) varied primarily by time (days since flood) and antecedent flow, but not spatial network position (i.e., drainage area). Intermittent sites exhibited high rates of ER (0.17–3.33 g dissolved oxygen [DO] m −2 d −1 ) following rewetting compared to perennial sites (0.03–1.17 g DO m −2 d −1 ), while GPP, NEP, and P/R were slower to recover and varied less between sites of differing preflood conditions. Metabolic rates were not strongly influenced by other environmental conditions. A large proportion of variation was explained by the random effect of location. Our results suggest that metabolism is temporally asynchronous and highly heterogenous across intermittent watersheds and that antecedent hydrology (drying prior to rewetting) stimulates heterotrophic activity, likely dependent on terrestrially derived organic matter and nutrient subsidies.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Non-Linear Device Head Coupling and Temporal Delays in Large Animal Acceleration Models of Traumatic Brain Injury - Andrew R. Mayer; Josef M. Ling; Declan A. Patton; David D. Stephenson; Andrew B. Dodd; Rebecca J. Dodd; Julie G. Rannou-Latella; Douglas H. Smith; Victoria E. Johnson; D. Kacy Cullen; Timothy B. Meier; Rachel E. Kinsler (Annals of Biomedical Engineering, 2022)
Accurate characterization of head kinematics following an external blow represents a fundamental aspect of traumatic brain injury (TBI) research. The majority of previous large animal studies have assumed an equivalent relationship between the device delivering the impulsive load and subsequent head kinematics rather than performing direct measurement (sensors or videography). The current study therefore examined factors affecting device/head coupling kinematics in an acceleration TBI model. Experiment 1 indicated ~ 50% reduction in peak angular velocity for swine head relative to the device, with an approximate doubling in temporal duration. The peak angular velocity for the head was not significantly altered by variations in restraint device (straps vs. cables), animal positioning or body mass. In Experiment 2, reducing the impulsive load by 32% resulted in only a 14% reduction in angular velocity of the head (approximately 69% head/device coupling ratio), with more pronounced differences qualitatively observed for angular momentum. A temporal delay was identified in initial device/head coupling, potentially a result of soft tissue deformation. Finally, similar head kinematics were obtained regardless of mounting the sensor directly to the skull or through the scalp (Experiment 3). Current findings highlight the importance of direct measurement of head kinematics for future studies.

A comparison of trends in population size and life history features of Atlantic salmon (Salmo salar) and anadromous and non-anadromous Brown trout (Salmo trutta) in a single catchment over 116 years - Colin E. Adams; Hannele M. Honkanen; Ellen Bryson; Isabel E. Moore; Malcolm MacCormick; Jennifer A. Dodd (Hydrobiologia, 2022)
We use a long time series of catch abundance from a recreational fishery over 116 years to look for population trends in Atlantic salmon, and anadromous (sea trout) and non-anadromous (brown) trout for a single catchment, Loch Lomond, west central Scotland. Year strongly predicted variation in catches but catch effort did not meaningfully increase explained variation. Salmon showed periods of increasing and decreasing trends, for sea trout and brown trout there was an overall declining trend. Since 1952, Lomond salmon population trends differed from both wider Scotland and southern Europe, indicating that the Lomond population is partially buffered from drivers of change in salmon populations more widely. In contrast Lomond sea trout showed a similar declining trend to that of populations from the wider west of Scotland over this period. The Lomond populations showed some evidence of shorter-term cycling patterns; the drivers for which are unknown. Body size in salmon and sea trout declined but increased in brown trout; salmon returned to freshwater later, and the relative proportion of all caught trout that were anadromous increased across the time series. This study shows a long and protracted period of fundamental change to populations of these two species over 116 years.

One beach amongst many: how weak fidelity to a focal nesting site can bias demographic rates in marine turtles - Joseph B. Pfaller; Sara M. Weaver; Kristina L. Williams; Mark G. Dodd; Matthew H. Godfrey; DuBose B. Griffin; S. Michelle Pate; C. George Glen; Campbell J. Nairn; Brian M. Shamblin (Marine Biology, 2022)

Shifting stoichiometry: Long‐term trends in stream‐dissolved organic matter reveal altered C:N ratios due to history of atmospheric acid deposition - Bianca M. Rodríguez‐Cardona; Adam S. Wymore; Alba Argerich; Rebecca T. Barnes; Susana Bernal; E. N. Jack Brookshire; Ashley A. Coble; Walter K. Dodds; Hannah M. Fazekas; Ashley M. Helton; Penny J. Johnes; Sherri L. Johnson; et al. (Global Change Biology, 2022)
Dissolved organic carbon (DOC) and nitrogen (DON) are important energy and nutrient sources for aquatic ecosystems. In many northern temperate, freshwater systems DOC has increased in the past 50 years. Less is known about how changes in DOC may vary across latitudes, and whether changes in DON track those of DOC. Here, we present long‐term DOC and DON data from 74 streams distributed across seven sites in biomes ranging from the tropics to northern boreal forests with varying histories of atmospheric acid deposition. For each stream, we examined the temporal trends of DOC and DON concentrations and DOC:DON molar ratios. While some sites displayed consistent positive or negative trends in stream DOC and DON concentrations, changes in direction or magnitude were inconsistent at regional or local scales. DON trends did not always track those of DOC, though DOC:DON ratios increased over time for ~30% of streams. Our results indicate that the dissolved organic matter (DOM) pool is experiencing fundamental changes due to the recovery from atmospheric acid deposition. Changes in DOC:DON stoichiometry point to a shifting energy‐nutrient balance in many aquatic ecosystems. Sustained changes in the character of DOM can have major implications for stream metabolism, biogeochemical processes, food webs, and drinking water quality (including disinfection by‐products). Understanding regional and global variation in DOC and DON concentrations is important for developing realistic models and watershed management protocols to effectively target mitigation efforts aimed at bringing DOM flux and nutrient enrichment under control.

Exploring genetic diversity of lowland avocado (Persea americana Mill.) as a genetic reservoir for breeding - Eduardo Sandoval-Castro; Ayesha Y. Peraza-Magallanes; Richard S. Dodd; Vanessa E. T. M. Ashworth; Abraham Cruz-Mendívil; Carlos L. Calderón-Vázquez (Genetic Resources and Crop Evolution, 2021)

Tidal Marsh Restoration Optimism in a Changing Climate and Urbanizing Seascape - Nathan J. Waltham; Caitlin Alcott; Myriam A. Barbeau; Just Cebrian; Rod M. Connolly; Linda A. Deegan; Kate Dodds; Lucy A. Goodridge Gaines; Ben L. Gilby; Christopher J. Henderson; Catherine M. McLuckie; Thomas J. Minello; et al. (Estuaries and Coasts, 2021)

Clinical Signs and Pathology Associated With Domoic Acid Toxicosis in Southern Sea Otters (Enhydra lutris nereis) - Melissa A. Miller; Megan E. Moriarty; Pádraig J. Duignan; Tanja S. Zabka; Erin Dodd; Francesca I. Batac; Colleen Young; Angelina Reed; Michael D. Harris; Katherine Greenwald; Raphael M. Kudela; Michael J. Murray; et al. (Frontiers in Marine Science, 2021)
The marine biotoxin domoic acid (DA) is an analog of the neurotransmitter glutamate that exerts potent excitatory activity in the brain, heart, and other tissues. Produced by the diatom Pseudo-nitzschia spp., DA accumulates in marine invertebrates, fish, and sediment. Southern sea otters ( Enhydra lutris nereis ) feed primarily on invertebrates, including crabs and bivalves, that concentrate and slowly depurate DA. Due to their high prey consumption (25% of body weight/day), sea otters are commonly exposed to DA. A total of 823 necropsied southern sea otters were examined to complete this study; first we assessed 560 subadult, adult, and aged adult southern sea otters sampled from 1998 through 2012 for DA-associated pathology, focusing mainly on the central nervous system (CNS) and cardiovascular system. We applied what was learned to an additional cohort of necropsied sea otters of all demographics (including fetuses, pups, juveniles, and otters examined after 2012: n = 263 additional animals). Key findings derived from our initial efforts were consistently observed in this more demographically diverse cohort. Finally, we assessed the chronicity of DA-associated pathology in the CNS and heart independently for 54 adult and aged adult sea otters. Our goals were to compare the temporal consistency of DA-associated CNS and cardiovascular lesions and determine whether multiple episodes of DA toxicosis could be detected on histopathology. Sea otters with acute, fatal DA toxicosis typically presented with neurological signs and severe, diffuse congestion and multifocal microscopic hemorrhages (microhemorrhages) in the brain, spinal cord, cardiovascular system, and eyes. The congestion and microhemorrhages were associated with detection of high concentrations of DA in postmortem urine or gastrointestinal content and preceded histological detection of cellular necrosis or apoptosis. Cases of chronic DA toxicosis often presented with cardiovascular pathology that was more severe than the CNS pathology; however, the lesions at both sites were relatively quiescent, reflecting previous damage. Sea otters with fatal subacute DA toxicosis exhibited concurrent CNS and cardiovascular pathology that was characterized by progressive lesion expansion and host response to DA-associated tissue damage. Acute, subacute, and chronic cases had the same lesion distribution in the CNS and heart. CNS pathology was common in the hippocampus, olfactory, entorhinal and parahippocampal cortex, periventricular neuropil, and ventricles. The circumventricular organs were identified as important DA targets; microscopic examination of the pituitary gland, area postrema, other circumventricular organs, and both eyes facilitated confirmation of acute DA toxicosis in sea otters. DA-associated histopathology was also common in cardiomyocytes and coronary arterioles, especially in the left ventricular free wall, papillary muscles, cardiac apex, and atrial free walls. Progressive cardiomyocyte loss and arteriosclerosis occurred in the same areas, suggesting a common underlying mechanism. The temporal stage of DA-associated CNS pathology matched the DA-associated cardiac pathology in 87% ( n = 47/54) of cases assessed for chronicity, suggesting that the same underlying process (e.g., DA toxicosis) was the cause of these lesions. This temporally matched pattern is also indicative of a single episode of DA toxicosis. The other 13% of examined otters ( n = 7/54) exhibited overlapping acute, subacute, or chronic DA pathology in the CNS and heart, suggestive of recurrent DA toxicosis. This is the first rigorous case definition to facilitate diagnosis of DA toxicosis in sea otters. Diagnosing this common but often occult condition is important for improving clinical care and assessing population-level impacts of DA exposure in this federally listed threatened subspecies. Because the most likely source of toxin is through prey consumption, and because humans, sea otters, and other animals consume the same marine foods, our efforts to characterize health effects of DA exposure in southern sea otters can provide strong collateral benefits.

In search of the “missing majority” of nesting loggerhead turtles: improved inter-seasonal recapture rates through subpopulation-scale genetic tagging - Brian M. Shamblin; Mark G. Dodd; S. Michelle Pate; Matthew H. Godfrey; Joseph B. Pfaller; Kristina L. Williams; Breanna L. Ondich; David A. Steen; Elizabeth S. Darrow; Paul Hillbrand; Ruth Boettcher; Michael S. Coyne; et al. (Marine Biology, 2021)

Spatial co‐localisation of extreme weather events: a clear and present danger - Rosalind J. Dodd; David R. Chadwick; Ian M. Harris; Adrian Hines; Dan Hollis; Theodoros Economou; Dylan Gwynn‐Jones; John Scullion; David A. Robinson; David L. Jones (Ecology Letters, 2021)
Extreme weather events have become a dominant feature of the narrative surrounding changes in global climate with large impacts on ecosystem stability, functioning and resilience; however, understanding of their risk of co‐occurrence at the regional scale is lacking. Based on the UK Met Office’s long‐term temperature and rainfall records, we present the first evidence demonstrating significant increases in the magnitude, direction of change and spatial co‐localisation of extreme weather events since 1961. Combining this new understanding with land‐use data sets allowed us to assess the likely consequences on future agricultural production and conservation priority areas. All land‐uses are impacted by the increasing risk of at least one extreme event and conservation areas were identified as the hotspots of risk for the co‐occurrence of multiple event types. Our findings provide a basis to regionally guide land‐use optimisation, land management practices and regulatory actions preserving ecosystem services against multiple climate threats.

Aquatic landscape change, extirpations, and introductions in the Chicago Region - M. Joseph Pasterski; Anthony Bellagamba; Stephanie Chancellor; Alister Cunje; Emily Dodd; Kerri Gefeke; Shannon Hsieh; Alec Schassburger; Alexis Smith; Wesley Tucker; Roy E. Plotnick (Urban Ecosystems, 2020)

Using path analysis to determine interacting effects of biotic and abiotic factors on patch-scale biogeochemical rates in a prairie stream - Matt T. Trentman; Walter K. Dodds; Keith B. Gido; Janine Rüegg; Claire M. Ruffing (Aquatic Sciences, 2020)

A mechanistic cohort study evaluating cognitive impairment in women treated for breast cancer - Janette L. Vardy; Myrle M. Stouten-Kemperman; Gregory Pond; Christopher M. Booth; Sean B. Rourke; Haryana M. Dhillon; Anna Dodd; Adrian Crawley; Ian F. Tannock (Brain Imaging and Behavior, 2019)

Removal of Woody Riparian Vegetation Substantially Altered a Stream Ecosystem in an Otherwise Undisturbed Grassland Watershed - Danelle M. Larson; Walter K. Dodds; Allison M. Veach (Ecosystems, 2019)

Spatial distribution bias in subject-specific abnormalities analyses - Andrew B. Dodd; Josef M. Ling; Edward J. Bedrick; Timothy B. Meier; Andrew R. Mayer (Brain Imaging and Behavior, 2018)

The Effect of Cations on Uranyl Transport and Fluorescence in Mesoporous Silica Gel - Brandon M. Dodd; Gary C. Tepper (Journal of Fluorescence, 2018)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

The influence of aquaculture unit proximity on the pattern of Lepeophtheirus salmonis infection of anadromous Salmo trutta populations on the isle of Skye, Scotland - I. Moore; J. A. Dodd; M. Newton; C. W. Bean; I. Lindsay; P. Jarosz; C. E. Adams (Journal of Fish Biology, 2018)
A total of 230 anadromous Salmo trutta (brown trout) were sampled in five sheltered coastal fjords (or sea lochs) on the Isle of Skye, Scotland, U.K., in 2016 at varying distances from active Atlantic salmon Salmo salar farms. Statistical models were developed to investigate potential correlations between salmon lice Lepeophtheirus salmonis burdens on S. trutta hosts and their proximity to S. salar farm cages. Significant correlations were found between lice burdens and fish fork length and proximity to the nearest S. salar farm. The probability of the presence of L. salmonis on fish hosts increased with fish host size and with distance from the nearest S. salar farm, but total lice burdens were highest in fish sampled near S. salar farms and decreased with distance. The proportion of different life‐cycle stages of L. salmonis were also dependent on S. salar farm proximity, with higher juvenile lice numbers recorded at sites near S. salar farm cages. These results highlight the complexity of the relationship between S. trutta and L. salmonis infections on wild fish and emphasize the requirement of further research to quantify these effects to better inform conservation and management strategies, particularly in areas of active S. salar farm facilities.

An evaluation of Z-transform algorithms for identifying subject-specific abnormalities in neuroimaging data - Andrew R. Mayer; Andrew B. Dodd; Josef M. Ling; Christopher J. Wertz; Nicholas A. Shaff; Edward J. Bedrick; Carlo Viamonte (Brain Imaging and Behavior, 2018)

The impact of a small-scale riverine obstacle on the upstream migration of Atlantic Salmon - M. Newton; J. A. Dodd; J. Barry; P. Boylan; C. E. Adams (Hydrobiologia, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

The effect of foraging and ontogeny on the prevalence and intensity of the invasive parasite Anguillicola crassus in the European eel Anguilla anguilla - J Barry; M Newton; J A Dodd; D Evans; J Newton; C E Adams (Journal of Fish Diseases, 2017)
Infection patterns of the invasive Anguillicola crassus nematode were investigated in a population of the European eel Anguilla anguilla where parasite invasion is very recent , Loch Lomond, Scotland. Intensity levels of the parasite were associated with differences in fish ontogeny and trophic ecology. Although eels foraged on both fish and invertebrates, individuals which were smaller and fed on invertebrates (>70% contribution to diet) were found to contain a greater number of swim bladder parasites compared to larger eel with a predominance of fish (>60% contribution) in their diet. Within affected fish, a significant negative relationship was found between fish length and parasite intensity, with smaller individuals having higher parasite intensity than larger individuals. This study indicates that food intake and infection risk are linked in this recently infected host–parasite system. From a management perspective increasing our understanding of how infection intensity and repeated exposure is linked to resource use in an ecosystem is important for the future management of this endangered species in Europe.

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Methods to estimate changes in soil water for phenotyping root activity in the field - W.R. Whalley; A. Binley; C.W. Watts; P. Shanahan; I.C. Dodd; E.S. Ober; R.W. Ashton; C.P. Webster; R.P. White; M. J. Hawkesford (Plant and Soil, 2017)

Improved female abundance and reproductive parameter estimates through subpopulation-scale genetic capture-recapture of loggerhead turtles - Brian M. Shamblin; Mark G. Dodd; DuBose B. Griffin; S. Michelle Pate; Matthew H. Godfrey; Michael S. Coyne; Kristina L. Williams; Joseph B. Pfaller; Breanna L. Ondich; Kimberly M. Andrews; Ruth Boettcher; Campbell J. Nairn (Marine Biology, 2017)

A prospective microstructure imaging study in mixed-martial artists using geometric measures and diffusion tensor imaging: methods and findings - Andrew R. Mayer; Josef M. Ling; Andrew B. Dodd; Timothy B. Meier; Faith M. Hanlon; Stefan D. Klimaj (Brain Imaging and Behavior, 2017)

Transitions in climate and energy discourse between Hurricanes Katrina and Sandy - Emily M. Cody; Jennie C. Stephens; James P. Bagrow; Peter Sheridan Dodds; Christopher M. Danforth (Journal of Environmental Studies and Sciences, 2017)

Spatial and temporal constraints on regional-scale groundwater flow in the Pampa del Tamarugal Basin, Atacama Desert, Chile - Richard S. Jayne; Ryan M. Pollyea; Justin P. Dodd; Elizabeth J. Olson; Susan K. Swanson (Hydrogeology Journal, 2016)

Spatial and successional dynamics of microbial biofilm communities in a grassland stream ecosystem - Allison M. Veach; James C. Stegen; Shawn P. Brown; Walter K. Dodds; Ari Jumpponen (Molecular Ecology, 2016)
Biofilms represent a metabolically active and structurally complex component of freshwater ecosystems. Ephemeral prairie streams are hydrologically harsh and prone to frequent perturbation. Elucidating both functional and structural community changes over time within prairie streams provides a general understanding of microbial responses to environmental disturbance. We examined microbial succession of biofilm communities at three sites in a third‐order stream at Konza Prairie over a 2‐ to 64‐day period. Microbial abundance (bacterial abundance, chlorophyll a concentrations) increased and never plateaued during the experiment. Net primary productivity (net balance of oxygen consumption and production) of the developing biofilms did not differ statistically from zero until 64 days suggesting a balance of the use of autochthonous and allochthonous energy sources until late succession. Bacterial communities (MiSeq analyses of the V4 region of 16S rRNA) established quickly. Bacterial richness, diversity and evenness were high after 2 days and increased over time. Several dominant bacterial phyla (Beta‐, Alphaproteobacteria, Bacteroidetes, Gemmatimonadetes, Acidobacteria, Chloroflexi) and genera ( Luteolibacter , Flavobacterium , Gemmatimonas , Hydrogenophaga ) differed in relative abundance over space and time. Bacterial community composition differed across both space and successional time. Pairwise comparisons of phylogenetic turnover in bacterial community composition indicated that early‐stage succession (≤16 days) was driven by stochastic processes, whereas later stages were driven by deterministic selection regardless of site. Our data suggest that microbial biofilms predictably develop both functionally and structurally indicating distinct successional trajectories of bacterial communities in this ecosystem.

Does size matter? A test of size‐specific mortality in Atlantic salmon Salmo salar smolts tagged with acoustic transmitters - M. Newton; J. Barry; J. A. Dodd; M. C. Lucas; P. Boylan; C. E. Adams (Journal of Fish Biology, 2016)
Mortality rates of wild Atlantic salmon Salmo salar smolts implanted with acoustic transmitters were assessed to determine if mortality was size dependent. The routinely accepted, but widely debated, ‘2% transmitter mass: body mass’ rule in biotelemetry was tested by extending the transmitter burden up to 12·7% of body mass in small [mean fork length ( L F ) 138·3 mm, range 115–168 mm] downstream migrating S. salar smolts. Over the short timescale of emigration (range 11·9–44·5 days) through the lower river and estuary, mortality was not related to S. salar size, nor was a relationship found between mortality probability and transmitter mass: body mass or transmitter length: L F ratios. This study provides further evidence that smolt migration studies can deviate from the ‘2% rule’ of thumb, to more appropriate study‐specific measures, which enables the use of fishes representative of the body size in natural populations without undue effects.

Lake bathymetry and species occurrence predict the distribution of a lacustrine apex predator - M. R. Hughes; J. A. Dodd; P. S. Maitland; C. E. Adams (Journal of Fish Biology, 2016)
This study examined the abiotic and biotic characteristics of ecosystems that allow expression of a life history called ferox trout, the colloquial name given to brown trout Salmo trutta adopting a piscivorous life history strategy, an apex predator in post‐glacial lakes in northern Europe. One hundred and ninety‐two lakes in Scotland show evidence of currently, or historically, supporting ferox S. trutta ; their presence was predicted in logistic models by larger and deeper lakes with a large catchment that also support populations of Arctic charr Salvelinus alpinus .

Early morning fluctuations in trunk diameter are highly sensitive to water stress in nectarine trees - J. M. De la Rosa; I. C. Dodd; R. Domingo; A. Pérez-Pastor (Irrigation Science, 2016)

Foraging specialisms influence space use and movement patterns of the European eel Anguilla anguilla - J. Barry; M. Newton; J. A. Dodd; O. E. Hooker; P. Boylan; M. C. Lucas; C. E. Adams (Hydrobiologia, 2016)

Freshwater and coastal migration patterns in the silver‐stage eel Anguilla anguilla - J. Barry; M. Newton; J. A. Dodd; M. C. Lucas; P. Boylan; C. E. Adams (Journal of Fish Biology, 2016)
The unimpeded downstream movement patterns and migration success of small female and male Anguilla anguilla through a catchment in north‐west Europe were studied using an acoustic hydrophone array along the River Finn and into the Foyle Estuary in Ireland. Twenty silver‐stage A. anguilla (total length, L T , range: 332–520 mm) were trapped 152 km upstream from a coastal marine sea‐lough outlet and internally tagged with acoustic transmitters of which 19 initiated downstream migration. Migration speed was highly influenced by river flow within the freshwater ( FW ) compartment. Anguilla anguilla activity patterns were correlated with environmental influences; light, tidal direction and lunar phase all influenced the initiation of migration of tagged individuals. Migration speed varied significantly between upstream and lower river compartments. Individuals migrated at a slower speed in transitional water and sea‐lough compartments compared with the FW compartment. While 88·5% survival was recorded during migration through the upper 121 km of the river and estuary, only 26% of A. anguilla which initiated downstream migration were detected at the outermost end of the acoustic array. Telemetry equipment functioned efficiently, including in the sea‐lough, so this suggests high levels of mortality during sea‐lough migration, or less likely, long‐term sea‐lough residence by silver A. anguilla emigrants. This has important implications for eel management plans.

Medical Advocacy and Supportive Environments for African-Americans Following Abnormal Mammograms - Yamile Molina; Bridgette H. Hempstead; Jacci Thompson-Dodd; Shauna Rae Weatherby; Claire Dunbar; Sarah D. Hohl; Rachel C. Malen; Rachel M. Ceballos (Journal of Cancer Education, 2015)

Effects of climate change on the delivery of soil‐mediated ecosystem services within the primary sector in temperate ecosystems: a review and New Zealand case study - Kate H. Orwin; Bryan A. Stevenson; Simeon J. Smaill; Miko U. F. Kirschbaum; Ian A. Dickie; Brent E. Clothier; Loretta G. Garrett; Tony J. van der Weerden; Michael H. Beare; Denis Curtin; Cecile A. M. de Klein; Michael B. Dodd; et al. (Global Change Biology, 2015)
Future human well‐being under climate change depends on the ongoing delivery of food, fibre and wood from the land‐based primary sector. The ability to deliver these provisioning services depends on soil‐based ecosystem services (e.g. carbon, nutrient and water cycling and storage), yet we lack an in‐depth understanding of the likely response of soil‐based ecosystem services to climate change. We review the current knowledge on this topic for temperate ecosystems, focusing on mechanisms that are likely to underpin differences in climate change responses between four primary sector systems: cropping, intensive grazing, extensive grazing and plantation forestry. We then illustrate how our findings can be applied to assess service delivery under climate change in a specific region, using New Zealand as an example system. Differences in the climate change responses of carbon and nutrient‐related services between systems will largely be driven by whether they are reliant on externally added or internally cycled nutrients, the extent to which plant communities could influence responses, and variation in vulnerability to erosion. The ability of soils to regulate water under climate change will mostly be driven by changes in rainfall, but can be influenced by different primary sector systems' vulnerability to soil water repellency and differences in evapotranspiration rates. These changes in regulating services resulted in different potentials for increased biomass production across systems, with intensively managed systems being the most likely to benefit from climate change. Quantitative prediction of net effects of climate change on soil ecosystem services remains a challenge, in part due to knowledge gaps, but also due to the complex interactions between different aspects of climate change. Despite this challenge, it is critical to gain the information required to make such predictions as robust as possible given the fundamental role of soils in supporting human well‐being.

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

A double-blind, placebo-controlled study evaluating the effects of caffeine and L-theanine both alone and in combination on cerebral blood flow, cognition and mood - F. L. Dodd; D. O. Kennedy; L. M. Riby; C. F. Haskell-Ramsay (Psychopharmacology, 2015)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Factors affecting the foraging behaviour of the European shag: implications for seabird tracking studies - L. M. Soanes; J. P. Y. Arnould; S. G. Dodd; G. Milligan; J. A. Green (Marine Biology, 2014)

Non-target impacts of the biocontrol agent Trichoderma atroviride on plant health and soil microbial communities in two native ecosystems in New Zealand - K. L. McLean; S. L. Dodd; R. F. Minchin; M. Ohkura; D. Bienkowski; A. Stewart (Australasian Plant Pathology, 2014)

Brain deposition and neurotoxicity of manganese in adult mice exposed via the drinking water - Saritha Krishna; Celia A. Dodd; Shahryar K. Hekmatyar; Nikolay M. Filipov (Archives of Toxicology, 2014)

Foraging habitats and migration corridors utilized by a recovering subpopulation of adult female loggerhead sea turtles: implications for conservation - DuBose B. Griffin; Sally R. Murphy; Michael G. Frick; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark G. Dodd; Matthew H. Godfrey; Brendan J. Godley; Lucy A. Hawkes; Thomas M. Murphy; Kristina L. Williams; et al. (Marine Biology, 2013)

A standardised protocol for the validation of banking methodologies for arterial allografts - R. J. Lomas; P. D. F. Dodd; P. Rooney; D. E. Pegg; P. A. Hogg; M. E. Eagle; K. E. Bennett; A. Clarkson; J. N. Kearney (Cell and Tissue Banking, 2013)

Woody Vegetation Removal Stimulates Riparian and Benthic Denitrification in Tallgrass Prairie - Alexander J. Reisinger; John M. Blair; Charles W. Rice; Walter K. Dodds (Ecosystems, 2013)

Genotypic variation in the ability of wheat roots to penetrate wax layers - W. R. Whalley; I. C. Dodd; C. W. Watts; C. P. Webster; A. L. Phillips; J. Andralojc; R. P. White; W. J. Davies; M. A. J. Parry (Plant and Soil, 2013)

Disease-Driven Amphibian Declines Alter Ecosystem Processes in a Tropical Stream - M. R. Whiles; R. O. Hall; W. K. Dodds; P. Verburg; A. D. Huryn; C. M. Pringle; K. R. Lips; S. S. Kilham; C. Colón-Gaud; A. T. Rugenski; S. Peterson; S. Connelly (Ecosystems, 2013)

Effects of different rates of Gaeumannomyces graminis var. tritici inoculum for detecting take-all suppression in soils - S. F. Chng; A. Stewart; M. G. Cromey; S. L. Dodd; R. C. Butler; M. V. Jaspers (Australasian Plant Pathology, 2013)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

Testing the metabolic theory of ecology - Charles A. Price; Joshua S Weitz; Van M. Savage; James Stegen; Andrew Clarke; David A. Coomes; Peter S. Dodds; Rampal S. Etienne; Andrew J. Kerkhoff; Katherine McCulloh; Karl J. Niklas; Han Olff; et al. (Ecology Letters, 2012)
The metabolic theory of ecology (MTE) predicts the effects of body size and temperature on metabolism through considerations of vascular distribution networks and biochemical kinetics. MTE has also been extended to characterise processes from cellular to global levels. MTE has generated both enthusiasm and controversy across a broad range of research areas. However, most efforts that claim to validate or invalidate MTE have focused on testing predictions. We argue that critical evaluation of MTE also requires strong tests of both its theoretical foundations and simplifying assumptions. To this end, we synthesise available information and find that MTE's original derivations require additional assumptions to obtain the full scope of attendant predictions. Moreover, although some of MTE's simplifying assumptions are well supported by data, others are inconsistent with empirical tests and even more remain untested. Further, although many predictions are empirically supported on average, work remains to explain the often large variability in data. We suggest that greater effort be focused on evaluating MTE's underlying theory and simplifying assumptions to help delineate the scope of MTE, generate new theory and shed light on fundamental aspects of biological form and function.

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

Genetic analysis of physiological components of salt tolerance conferred by Solanum rootstocks. What is the rootstock doing for the scion? - M. J. Asins; M. C. Bolarín; F. Pérez-Alfocea; M. T. Estañ; C. Martínez-Andújar; A. Albacete; I. Villalta; G. P. Bernet; Ian C. Dodd; E. A. Carbonell (Theoretical and Applied Genetics, 2010)

Effects of modafinil and methylphenidate on visual attention capacity: a TVA-based study - Kathrin Finke; Chris M. Dodds; Peter Bublak; Ralf Regenthal; Frank Baumann; Tom Manly; Ulrich Müller (Psychopharmacology, 2010)

Dye-tracing studies in southwestern Missouri, USA: indication of stratigraphic flow control in the Burlington Limestone - Douglas Gouzie; Rebecca P. Dodd; David M. White (Hydrogeology Journal, 2010)

The dopamine D2 receptor antagonist sulpiride modulates striatal BOLD signal during the manipulation of information in working memory - Chris M. Dodds; Luke Clark; Anja Dove; Ralf Regenthal; Frank Baumann; Ed Bullmore; Trevor W. Robbins; Ulrich Müller (Psychopharmacology, 2009)

De novo synthesis of human dermis in vitro in the absence of a three-dimensional scaffold - Tara Pouyani; Vincent Ronfard; Paul G. Scott; Carole M. Dodd; Aftab Ahmed; Richard L. Gallo; Nancy L. Parenteau (In Vitro Cellular & Developmental Biology - Animal, 2009)

Tetranucleotide markers from the loggerhead sea turtle (Caretta caretta) and their cross-amplification in other marine turtle species - Brian M. Shamblin; Brant C. Faircloth; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Peter H. Dutton; Amy Frey; Campbell J. Nairn (Conservation Genetics, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Headwater Influences on Downstream Water Quality - Walter K. Dodds; Robert M. Oakes (Environmental Management, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Different native arbuscular mycorrhizal fungi influence the coexistence of two plant species in a highly alkaline anthropogenic sediment - Rui S. Oliveira; Paula M. L. Castro; John C. Dodd; Miroslav Vosátka (Plant and Soil, 2006)

Controls on Nutrients Across a Prairie Stream Watershed: Land Use and Riparian Cover Effects - Walter K. Dodds; Robert M. Oakes (Environmental Management, 2006)

Studies on the diversity of arbuscular mycorrhizal fungi and the efficacy of two native isolates in a highly alkaline anthropogenic sediment - R. S. Oliveira; M. Vosátka; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2005)

Differential expression of the GABA transporters GAT-1 and GAT-3 in brains of rats, cats, monkeys and humans - David V. Pow; Robert K. P. Sullivan; Susan M. Williams; Heather L. Scott; Peter R. Dodd; David Finkelstein (Cell and Tissue Research, 2005)

The effects of phosphorus nutrition and soil pH on the growth of some ancient woodland indicator plants and their interaction with competitor species - N. A. Hipps; M. J. Davies; P. Dodds; G. P. Buckley (Plant and Soil, 2005)

Rapid screening of invertebrate predators for multiple prey DNA targets - G. L. HARPER; R. A. KING; C. S. DODD; J. D. HARWOOD; D. M. GLEN; M. W. BRUFORD; W. O. C. SYMONDSON (Molecular Ecology, 2005)
DNA‐based techniques are providing valuable new approaches to tracking predator–prey interactions. The gut contents of invertebrate predators can be analysed using species‐specific primers to amplify prey DNA to confirm trophic links. The problem is that each predator needs to be analysed with primers for the tens of potential prey available at a field site, even though the mean number of species detected in each gut may be as few as one or two. Conducting all these PCRs (polymerase chain reactions) is a lengthy process, and effectively precludes the analysis of the hundreds of predators that might be required for a meaningful ecological study. We report a rapid, more sensitive and practical approach. Multiplex PCRs, incorporating fluorescent markers, were found to be effective at amplifying degraded DNA from predators’ guts and could amplify mitochondrial DNA fragments from 10+ species simultaneously without ‘drop outs’. The combined PCR products were then separated by size on polyacrylamide gels on an ABI377 sequencer. New primers to detect the remains of aphids, earthworms, weevils and molluscs in the guts of carabid predators were developed and characterized. The multiplex‐sequencer approach was then applied to field‐caught beetles, some of which contained DNA from as many as four different prey at once. The main prey detected in the beetles proved to be earthworms and molluscs, although aphids and weevils were also consumed. The potential of this system for use in food‐web research is discussed.

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

Resistance and Resilience of Macroinvertebrate Assemblages to Drying and Flood in a Tallgrass Prairie Stream System - Ken M. Fritz; Walter K. Dodds (Hydrobiologia, 2004)

Integrating diel starch metabolism with the circadian and environmental regulation of Crassulacean acid metabolism in Mesembryanthemum crystallinum - Antony N. Dodd; Howard Griffiths; Tahar Taybi; John C. Cushman; Anne M. Borland (Planta, 2003)

Interaction of blood flow and oxygen delivery affects peak $$\dot V{\rm O}_2 $$ and fatigue in canine muscle in situ - Ioannis S. Vrabas; Stephen L. Dodd; Pat M. Crawford (European Journal of Applied Physiology, 2002)

A comparison of the trophic ecology of the crayfishes (Orconectes nais (Faxon) and Orconectes neglectus (Faxon)) and the central stoneroller minnow ( Campostoma anomalum (Rafinesque)): omnivory in a tallgrass prairie stream - Michelle Evans-White; Walter K. Dodds; Lawrence J. Gray; Ken M. Fritz (Hydrobiologia, 2001)

The mycorrhizal status of Phragmites australis in several polluted soils and sediments of an industrialised region of Northern Portugal - R.S. Oliveira; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2001)

A genetic map of the Nicotiana alata S locus that includes three pollen-expressed genes - J.-H. Li; N. Nass; M. Kusaba; P. N. Dodds; N. Treloar; A. E. Clarke; E. Newbigin (Theoretical and Applied Genetics, 2000)

Molecular Characterization of an Isolate of Citrus Tristeza Virus that Causes Severe Symptoms in Sweet Orange - Zhong-Nan Yang; Deborah M. Mathews; J. Allan Dodds; T. Erik Mirkov (Virus Genes, 1999)

Effect of Western Spruce Budworm Defoliation on the Physiology and Growth of Potted Douglas-Fir Seedlings - Thomas E. Kolb; Kimberly A. Dodds; Karen M. Clancy (Forest Science, 1999)
Interactions between effects of insect defoliators on tree physiology and growth and soil nutrient and water availability are poorly understood. We addressed whether the western spruce budworm influences nutrient and water relations, ectomycorrhizae, leaf gas exchange, and growth of Douglas-fir seedlings under different environmental conditions. Four-year-old, potted seedlings were grown in two soil types (basalt-derived, limestone-derived) with two levels of soil moisture (high, low) and were subjected to three levels of budworm defoliation (none, moderate, heavy) and two levels of frass and litter produced by budworm feeding (with, without) over 2 yr in a greenhouse environment. Defoliation, soil moisture, and soil type influenced allocation of seedling biomass to leaves, stems, and roots. The addition of frass and litter had no effect on any measured soil or tree characteristic. Interactions between defoliation and other experimental factors were not important except for the defoliation x soil moisture interaction where heavy defoliation reduced the negative effects of low soil moisture on seedling predawn water potential, net photosynthetic rate, and stomatal conductance. Heavily defoliated seedlings had less biomass, higher foliar concentrations of N, Ca, and Mg, less ectomycorrhizae, and higher net photosynthetic rate and stomatal conductance compared with nondefoliated seedlings. For. Sci. 45(2):280-291.

Differential water resource use by herbaceous and woody plant life-forms in a shortgrass steppe community - M. B. Dodd; W. K. Lauenroth; J. M. Welker (Oecologia, 1998)

The role of different arbuscular mycorrhizal fungi in the growth of Calamagrostis villosa and Deschampsia flexuosa, in experiments with simulated acid rain - M. Vosatka; J.C. Dodd (Plant and Soil, 1998)

A second-generation linkage map of the sheep genome - Maurico J. de Gortari; Brad A. Freking; Rachel P. Cuthbertson; Steven M. Kappes; John W. Keele; Roger T. Stone; Kreg A. Leymaster; Ken G. Dodds; Allan M. Crawford; Craig W. Beattie (Mammalian Genome, 1998)

The influence of soil texture on the soil water dynamics and vegetation structure of a shortgrass steppe ecosystem - M. B. Dodd; W. K. Lauenroth (Plant Ecology, 1997)

Protein engineering of lantibiotics - Oscar P. Kuipers; Gabriele Bierbaum; Birgit Ottenwälder; Helen M. Dodd; Nicky Horn; Jörg Metzger; Thomas Kupke; Volker Gnau; Roger Bongers; Patrick van den Bogaard; Hans Kosters; Harry S. Rollema; et al. (Antonie van Leeuwenhoek, 1996)